The Soybean Basic Helix-Loop-Helix Transcription Factor ORG3-Like Enhances Cadmium Tolerance via Increased Iron and Reduced Cadmium Uptake and Transport from Roots to Shoots - Xu, Zhaolong; Liu, Xiaoqing; He, Xiaolan; Xu, Ling; Huang, Yihong; Shao, Hongbo; Zhang, Dayong; Tang, Boping; Ma, Hongxiang (Frontiers in Plant Science, 2017)
Cadmium (Cd) is one of the most dangerous heavy metal pollutants in the environment and is toxic to animal and plant cells. On the other hand, iron (Fe) is an essential element for plant growth and development. Under Cd exposure, plants display leaf chlorosis, which is a typical symptom of Fe deficiency. Recently, several Arabidopsis basic/helix-loop-helix (bHLH) transcription factors have been identified that are involved in the interactions between Cd and Fe. In the present study, over-expression the ORG3-like gene GmORG3, a bHLH transcription factor OBP3-responsive gene (ORG), enhanced Cd tolerance and stabilized Fe homeostasis. The domain analysis of GmORG3 showed that the protein contains a conserved 61-residue bHLH domain belonging to subfamily II. Moreover, subcellular localization experiments showed that GmORG3 is a nucleoprotein. GmORG3 was transcribed only in soybean roots and was significantly induced by external Cd stress in soybean plants. Heterologous expression of GmORG3 enhanced Cd tolerance in yeast. Furthermore, the overexpression of GmORG3 in soybean mosaic seedlings using a hairy root system showed that overexpressing plants increased the translocation ratio of Fe but reduced Cd translocation from the roots to shoots. In addition, the ectopic expression of GmORG3 in tobacco reduced phytotoxic effects induced by Cd stress and Fe deficiency, including the blockage of root elongation and decreased chlorophyll content. By integrating all these results, we found that GmORG3 plays an important role in response to Cd stress. The results provide new insights into the molecular mechanisms of Cd tolerance in soybean.